دراسة وتقييم الإهتزازات الميكانيكية باستخدام الحاسوب - لبان نديمة (Latakia University Journal -Engineering Sciences Series, 2017)
تتطور صناعة الآلات من أجل زيادة سرعتها وقدرتها وإنتاجيتها، لكن ذلك يترافق مع زيادة التأثيرات الميكانيكية والحمولات الديناميكية بين عناصر وأجزاء تلك الآلات، مما يؤدي إلى نشوء الإهتزازات الميكانيكية فيها والتي تسبب بدورها أضرارا بالغة في الآلات وتؤثر بشكل سلبي على المحيط الذي تتواجد فيه . تعتبر دراسة الإهتزازات الميكانيكية ذات أهمية بالغة لطلاب العلوم الهندسية والتقنية لمعرفة الإهتزازات التي يمكن أن تنشأ في الآلة التي يجري تصميمها، أو دراسة الإهتزازات الحاصلة في الآلات قيد الإستثمار لعزلها والتقليل من آثارها السلبية. لذلكتم إعداد برنامج نمذجة يوضح طريقة لنمذجة بعض الموديلات الرياضية التي تمثل بعض حالات الإهتزازات الممكنة ويحدد أهم البارامترات التي تصف الحركات الإهتزازية المختلفة، حيث تم اختيار لغة برمجة ملائمة لدمج وإظهار الرسوم والشروحات النصية ومحاكاة الحركة الحاصلة في برنامج واحد، وقد طبق البرنامج على أنواع مختلفة من مسائل الإهتزازات،حيث يتيح عرضها بشكل بسيط وسهل من خلال دقة قيم البارامترات الناتجة مقارنة مع لغات برمجية أخرى مختلفة. Machine developing aimsto improve its velocity, capability and production,this is accompanied by increase of Mechanical side effects and the dynamical loads between the Machines elements and parts, that may conduct to rise the Mechanical vibrations and may cause a lot of damage in these machines, and cause negative effects on the environmentaround these machines, the study of Mechanical vibrations has a significant importance for engineering and technical students, to have knowledge of Mechanical vibrations that may arise in the machines under design process, or to study the mechanical vibrations resulting in the machines under use to isolate these vibrations and attenuate of its negative effects, for that we introduced an simulation program to show and illustrate a method to simulate some mathematical models representing some of possible types of vibrations, and to determine the most important parameters that describe the different vibrations motions, we choose an suitable programing language to merge this simulated models with an illustration and learning texts and drawings and animations in one executable application, this application show the models and the results in simple and very clear manner, and show the results in high resolution comparing with other programing languages.